Gait generation via the Foot Placement Estimator for 3D bipedal robots - Choudhury, Safwan; Kulic, Dana (2013 IEEE International Conference on Robotics and Automation, 2013)
This paper proposes a trajectory generation and control strategy for generating stable gait subject to unknown disturbances, based on the concept of the Foot Placement Estimator (FPE). While most walking control strategies in the field of bipedal locomotion aim to constantly maintain balance, the Foot Placement Estimator (FPE) estimates where the foot must be placed in order to restore balance. One of the key novelties of the FPE approach is its natural extension to form complete gait cycles using a state machine and simple proportional-derivative controllers. In this paper, the FPE control strategy is extended from 2D to 3D robots, and demonstrated in simulation on a 14-DOF lower body bipedal robot.